The relationship between level of mother’s education and knowledge about posyandu with active mother toddler in posyandu activities at PKM Kayu Manis Bogor City - amanah eva fidusia (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2022)
Abstract Posyandu is a program to empower the community and make it easier for the community to obtain health services. The most dominanted factor influencing is the level of education and knowledged of mothers. The purpose of this studied was to see the relationship between level of mother’s education and knowledged of mothers about posyandu with the activeness of mothers under five in Integrated Healthcare Center activities at PKM Kayu Manis Bogor City. The type of research is used quantitative with a cross-sectional approach. The sample of research is used from mother’s who had toddler and brought their toddler at posyandu PKM Kayu manis as many as 106 mothers used Simple Random Sampling method. The data analysis used was univariate analysis and bivariate analysis using the chi-square statistical test with SPSS version 21. The results of the chi-square test showed that there was no relationship between education level and mother's activity (p=0.253) and there was no relationship between mother's knowledge and mother's activity (p=0.967) in posyandu activities at PKM Kayu Manis Bogor City. Based on the results of the research, the integrated service post manager can improved and developed more attractive programs so that the community can optimally utilize the integrated service post facility in obtained information. Keywords: education, knowledge, mother's activity, posyandu